AUTHOR’S INTUITION AND INTROSPECTION IN THE PROCESS OF FORMATION AND REALISATION OF SYNONYMIC STRUCTURES (BASED ON MODERN FRENCH FICTION) - Anastasiia V. Lepetiukha. (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The article studies intuitive mechanisms of sublinguistic schemes, primary structures and synonymic transforms formation in modern French fiction and mechanisms of synonymic preferential options actualization in correlation with the (auto)observation. This led to the use of the introspection method, the procedure of inverse reconstruction (discourse → language) of virtual (linguistic) transformational processes and the “alternative” linguistic experiment consisting in the artificial substitution of some utterance by a synonymic one. The goal of the article is to study intuitive mechanisms of synonymic constructions creation and realization in correlation with the observation of the facts and events of the real world and the introspection, alongside with the inverse reconstruction of the virtual transformational processes as an “alternative” linguistic experiment strategy. In the course of analysis we have found that the prearranged situation correlates with the addresser’s observation of the facts of reality, and that the mechanisms of prelinguistic, linguistic and discourse intuitions work at the level of three components of G. Guillaume’s speech act causation – mental operations → language → discourse, that is in the process of unconscious, subconscious and conscious activity of psychomechanisms (cognitive polyoperations) – and correlate with the introspection. It was proved that formation, exteriorization and interiorization of synonymic discourse innovations is the bidirectional process. The addressee reveals the author’s communicative intention to simplify or to complicate the information and the peculiarities of his/her idiostyle through two stages of the “alternative” linguistic experiment. First stage is an inverse reconstruction of the primary structure and extended, reduced and equal by quantity ludic and non-ludic synonymic transformants (microfields) of the functional-semantic macrofield virtual synonymic series by means of exteriorized synonymic discourse innovations observation and interiorization as a result of the author’s observation of facts of objective reality – introspection which cover the prelinguistic, linguistic and discursive intuitions. Second stage is to determine the degree of co(n)textual (linguistic and / or situational) pertinence of each member in synonymic series and to justify preferential option co(n)textual adequation. It was revealed that the inverse reconstruction is possible to realize only up to the primary structure which is formed in the process of the conscious activity of psychomechanisms because the pre-linguistic cognitive polyoperations and subconscious sublinguistic schemes aren’t available for the analysis of information recipient.